1991
DOI: 10.1346/ccmn.1991.0390602
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of a Chromian Muscovite to Kaolinite

Abstract: --Single crystal X-ray diffraction and electron-optical analysis were used to investigate the weathering of a chromium-bearing muscovite (fuchsite). The muscovite had mostly altered to kaolinite with minor amounts ofhalloysite occurring between kaolinite plates. Evidence for both epitactic and topotactic growth of kaolinite from muscovite was obtained and no intermediate poorly-crystalline phases were detected. About half of the Cr in fuchsite was incorporated into kaolinite, whereas most of the Ti, Fe and Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Their relative abundances were known to change within one weathering profile, or from one to another profile (Parham, 1969). Transformations between the two minerals after their early formation may change their relative abundances, as suggested by thermodynamic and kinetic simulation (Steefel and Van Cappellen, 1990), by microscopic observations (Churchman and Gilkes, 1989;Robertson and Eggleton, 1991;Singh and Gilkes, 1992;Singh and Mackinnon, 1996;Jeong, 1998a), and by structural modeling (Singh, 1996). The abundances of kaolin minerals in the relatively young weathering profile appear to be largely controlled by the different formation processes because transformations require time.…”
Section: Introductionmentioning
confidence: 99%
“…Their relative abundances were known to change within one weathering profile, or from one to another profile (Parham, 1969). Transformations between the two minerals after their early formation may change their relative abundances, as suggested by thermodynamic and kinetic simulation (Steefel and Van Cappellen, 1990), by microscopic observations (Churchman and Gilkes, 1989;Robertson and Eggleton, 1991;Singh and Gilkes, 1992;Singh and Mackinnon, 1996;Jeong, 1998a), and by structural modeling (Singh, 1996). The abundances of kaolin minerals in the relatively young weathering profile appear to be largely controlled by the different formation processes because transformations require time.…”
Section: Introductionmentioning
confidence: 99%
“…Muscovite-kaolinite intergrowths occur under a range of environmental conditions: weathering of soils (Banfield and Eggleton, 1990;Singh and Gilkes, 1991;Jeong, 1998), hydrothermal alteration (Craw et al, 1982;Jiang and Peacor, 1991) and different stages of diagenesis, e.g. early (Crowley, 1991) and advanced diagenesis, (Marfil and Gomez Gras, 1992) and subsequent uplift (Jiang et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Ga (Martin et al 1998) and Cu in the octahedra of synthetic kaolinites has been confirmed recently. Chromium substitutions were proved in natural samples (Brookins 1973;Maksimovic and Brindley 1980;Macksimovic et al 1981;Singh and Gilkes 1991;Mosser et al 1993;Gaite and Mosser 1993). Titanium is also considered as a potential candidate for substitution in kaolinites (Jepson and Rowse 1975;Rengasamy 1976;Weaver 1976).…”
Section: Introductionmentioning
confidence: 99%